IDNLearn.com offers a reliable platform for finding accurate and timely answers. Ask your questions and receive reliable, detailed answers from our dedicated community of experts.
Sagot :
Sure! Let's solve each product step by step.
### 1. [tex]\((3x)\left(x^2 y^3\right)\)[/tex]
- Step 1: Identify the coefficients and variables in each term. Here, [tex]\(3x\)[/tex] and [tex]\(x^2 y^3\)[/tex].
- Step 2: Multiply the coefficients: [tex]\(3\)[/tex].
- Step 3: Apply the product rule for exponents: [tex]\(a^m \cdot a^n = a^{m+n}\)[/tex].
- For [tex]\(x\)[/tex]: [tex]\(x \cdot x^2 = x^{1+2} = x^3\)[/tex].
- For [tex]\(y\)[/tex]: Since [tex]\(y^3\)[/tex] does not have another [tex]\(y\)[/tex] term to multiply with, it stays as [tex]\(y^3\)[/tex].
Thus, the product is:
[tex]\[3x^3y^3\][/tex]
### 2. [tex]\(\left(5 a^3 b\right)(2 a b)\)[/tex]
- Step 1: Identify the coefficients and variables: [tex]\(5a^3b\)[/tex] and [tex]\(2ab\)[/tex].
- Step 2: Multiply the coefficients: [tex]\(5 \cdot 2 = 10\)[/tex].
- Step 3: Apply the product rule for exponents:
- For [tex]\(a\)[/tex]: [tex]\(a^3 \cdot a = a^{3+1} = a^4\)[/tex].
- For [tex]\(b\)[/tex]: [tex]\(b \cdot b = b^{1+1} = b^2\)[/tex].
Thus, the product is:
[tex]\[10a^4b^2\][/tex]
### 3. [tex]\(\left(18 y^2 x^3 z\right)\left(3 x^8 y^6 z^4\right)\)[/tex]
- Step 1: Identify the coefficients and variables: [tex]\(18y^2x^3z\)[/tex] and [tex]\(3x^8y^6z^4\)[/tex].
- Step 2: Multiply the coefficients: [tex]\(18 \cdot 3 = 54\)[/tex].
- Step 3: Apply the product rule for exponents:
- For [tex]\(y\)[/tex]: [tex]\(y^2 \cdot y^6 = y^{2+6} = y^8\)[/tex].
- For [tex]\(x\)[/tex]: [tex]\(x^3 \cdot x^8 = x^{3+8} = x^{11}\)[/tex].
- For [tex]\(z\)[/tex]: [tex]\(z \cdot z^4 = z^{1+4} = z^5\)[/tex].
Thus, the product is:
[tex]\[54y^8x^{11}z^5\][/tex]
### 4. [tex]\((2xyz)\left(-4x^2yz\right)\)[/tex]
- Step 1: Identify the coefficients and variables: [tex]\(2xyz\)[/tex] and [tex]\(-4x^2yz\)[/tex].
- Step 2: Multiply the coefficients: [tex]\(2 \cdot -4 = -8\)[/tex].
- Step 3: Apply the product rule for exponents:
- For [tex]\(x\)[/tex]: [tex]\(x \cdot x^2 = x^{1+2} = x^3\)[/tex].
- For [tex]\(y\)[/tex]: [tex]\(y \cdot y = y^{1+1} = y^2\)[/tex].
- For [tex]\(z\)[/tex]: [tex]\(z \cdot z = z^{1+1} = z^2\)[/tex].
Thus, the product is:
[tex]\[-8x^3y^2z^2\][/tex]
So, the final results for the products are:
1. [tex]\(3x^3y^3\)[/tex]
2. [tex]\(10a^4b^2\)[/tex]
3. [tex]\(54y^8x^{11}z^5\)[/tex]
4. [tex]\(-8x^3y^2z^2\)[/tex]
### 1. [tex]\((3x)\left(x^2 y^3\right)\)[/tex]
- Step 1: Identify the coefficients and variables in each term. Here, [tex]\(3x\)[/tex] and [tex]\(x^2 y^3\)[/tex].
- Step 2: Multiply the coefficients: [tex]\(3\)[/tex].
- Step 3: Apply the product rule for exponents: [tex]\(a^m \cdot a^n = a^{m+n}\)[/tex].
- For [tex]\(x\)[/tex]: [tex]\(x \cdot x^2 = x^{1+2} = x^3\)[/tex].
- For [tex]\(y\)[/tex]: Since [tex]\(y^3\)[/tex] does not have another [tex]\(y\)[/tex] term to multiply with, it stays as [tex]\(y^3\)[/tex].
Thus, the product is:
[tex]\[3x^3y^3\][/tex]
### 2. [tex]\(\left(5 a^3 b\right)(2 a b)\)[/tex]
- Step 1: Identify the coefficients and variables: [tex]\(5a^3b\)[/tex] and [tex]\(2ab\)[/tex].
- Step 2: Multiply the coefficients: [tex]\(5 \cdot 2 = 10\)[/tex].
- Step 3: Apply the product rule for exponents:
- For [tex]\(a\)[/tex]: [tex]\(a^3 \cdot a = a^{3+1} = a^4\)[/tex].
- For [tex]\(b\)[/tex]: [tex]\(b \cdot b = b^{1+1} = b^2\)[/tex].
Thus, the product is:
[tex]\[10a^4b^2\][/tex]
### 3. [tex]\(\left(18 y^2 x^3 z\right)\left(3 x^8 y^6 z^4\right)\)[/tex]
- Step 1: Identify the coefficients and variables: [tex]\(18y^2x^3z\)[/tex] and [tex]\(3x^8y^6z^4\)[/tex].
- Step 2: Multiply the coefficients: [tex]\(18 \cdot 3 = 54\)[/tex].
- Step 3: Apply the product rule for exponents:
- For [tex]\(y\)[/tex]: [tex]\(y^2 \cdot y^6 = y^{2+6} = y^8\)[/tex].
- For [tex]\(x\)[/tex]: [tex]\(x^3 \cdot x^8 = x^{3+8} = x^{11}\)[/tex].
- For [tex]\(z\)[/tex]: [tex]\(z \cdot z^4 = z^{1+4} = z^5\)[/tex].
Thus, the product is:
[tex]\[54y^8x^{11}z^5\][/tex]
### 4. [tex]\((2xyz)\left(-4x^2yz\right)\)[/tex]
- Step 1: Identify the coefficients and variables: [tex]\(2xyz\)[/tex] and [tex]\(-4x^2yz\)[/tex].
- Step 2: Multiply the coefficients: [tex]\(2 \cdot -4 = -8\)[/tex].
- Step 3: Apply the product rule for exponents:
- For [tex]\(x\)[/tex]: [tex]\(x \cdot x^2 = x^{1+2} = x^3\)[/tex].
- For [tex]\(y\)[/tex]: [tex]\(y \cdot y = y^{1+1} = y^2\)[/tex].
- For [tex]\(z\)[/tex]: [tex]\(z \cdot z = z^{1+1} = z^2\)[/tex].
Thus, the product is:
[tex]\[-8x^3y^2z^2\][/tex]
So, the final results for the products are:
1. [tex]\(3x^3y^3\)[/tex]
2. [tex]\(10a^4b^2\)[/tex]
3. [tex]\(54y^8x^{11}z^5\)[/tex]
4. [tex]\(-8x^3y^2z^2\)[/tex]
We greatly appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. Thank you for trusting IDNLearn.com with your questions. Visit us again for clear, concise, and accurate answers.